The effectiveness of tepid water sponge on reducing body temperature in children with hyperthermia: A meta-analysis - Widiyanto, Aris; Yuniarti, Tri; Mustain, Mustain; Putri, Santy Irene; Anulus, Ayu; Atmojo, Joko Tri (Universitas Aisyah Pringsewu, 2023)
Background: Hypothermia occurs when the body temperature rises above normal due to external factors, namely exposure to high temperatures or heat sources. This meta-analysis was conducted to assess the effectiveness of warm water spongee compresses in reducing children body temperature by synthesizing previous studies so that they can provide clinical information on clinical practice, guideline development and further research. This studyy aims to assess the effectivenesss of warm water sponge compresses to reduce fever in hyperthermic children Methods: This main article was obtained from online databases (Elsevier, Google Scholar, Science Direct, and PubMed) with a period of 2012-2022. Population: children. Intervention: warm water sponge. Comparison: usual care. Result: body temperature. For searching primary articles used the keywords (Warm water sponge) OR (Warm therapy) AND (Body temperature) AND (children) AND Mean SD. Articles were screened using the PRISMA fflow diagram. Primary article analysis with the Review Manager 5.3 application. Results: The data that has been processed shows that Children with hyperthermia who received the tepid water sponge therapy experienced a decrease in temperature 1.35 units lower compared to children who were only given usual care therapy, (SMD = -1.31; 95% CI = -1.61 to -1.09; p less than 0.001). Conclusion: Warm water sponge compresses can be used as initial therapy to reduce body temperature in hyperthermic children Recommendation: Warm water sponge compresses can be recommended as an effective initial treatment to reduce body temperature in hyperthermic children.